The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00134-016-4394-4
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired pneumonia related to intracellular pathogens

Abstract: Community-acquired pneumonia (CAP) is associated with high rates of morbidity and mortality worldwide; the annual incidence of CAP among adults in Europe has ranged from 1.5 to 1.7 per 1000 population. Intracellular bacteria are common causes of CAP. However, there is considerable variation in the reported incidence between countries and change over time. The intracellular pathogens that are well established as causes of pneumonia are Legionella pneumophila, Mycoplasma pneumoniae, Chlamydophila pneumoniae, Chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 101 publications
2
73
1
3
Order By: Relevance
“…Moreover, performing standard serologic tests on all patients with CAP is not common practice. The intracellular pathogens that are well-established as causes of CAP are: Legionella pneumophila , Mycoplasma pneumoniae , Chlamydophila pneumoniae , Chlamydophila psittaci and Coxiella burnetii [18,19]. No clinical features exist that make it possible to distinguish intracellular pathogens from classical pathogens (pneumococcus) in pneumonia, although extra-pulmonary manifestations are often associated with intracellular pathogens in CAP [20].…”
Section: Microbial Etiology Of Community-acquired Pneumonia (Cap)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, performing standard serologic tests on all patients with CAP is not common practice. The intracellular pathogens that are well-established as causes of CAP are: Legionella pneumophila , Mycoplasma pneumoniae , Chlamydophila pneumoniae , Chlamydophila psittaci and Coxiella burnetii [18,19]. No clinical features exist that make it possible to distinguish intracellular pathogens from classical pathogens (pneumococcus) in pneumonia, although extra-pulmonary manifestations are often associated with intracellular pathogens in CAP [20].…”
Section: Microbial Etiology Of Community-acquired Pneumonia (Cap)mentioning
confidence: 99%
“…A recent review article [19] reported that severe CAP caused by intracellular pathogens accounts for approximately 1% to 7% of cases [6,8,21]. Since antimicrobial therapy for severe pneumonia is empiric and covers typical pathogens and the principal intracellular pathogens, results of microbiological diagnosis have an important relationship with the clinical prognosis of pneumonia.…”
Section: Microbial Etiology Of Community-acquired Pneumonia (Cap)mentioning
confidence: 99%
“…Pneumonia is a common lung disease which is responsible for significant morbidity and mortality worldwide [1,2]. Community-acquired pneumonia (CAP) is the main type of pneumonia which can also result in high risk of mortality in critically-ill patients [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In the adult population, acceptance of an AST intervention has also been associated with a trend toward reduced mortality on multivariable analysis. Moreover, nucleic acid amplification testing and mass spectrometry can identify selected antibiotic resistance patterns to vancomycin (VanA/ VanB), methicillin (MecA), cephalosporins (beta-lactamases) and carbapenem (CPE) [4].Polymerase chain reaction (PCR) is well established for the diagnosis of "atypical" pathogens in severe community-acquired pneumonia [6] and for the study of ARDS with possible infectious etiology, namely for respiratory viruses (HSV and CMV), with virus load quantification, and also for Pneumocystis and Aspergillus [5]. In a retrospective case-control study in adult ICU patients with pneumonia and severe sepsis or septic shock, a strategy with bronchoalveolar lavage (BAL) cultures plus BAL M-PCR led to higher microbiological yield and less time to antibiotic therapy modification compared to a BAL culture strategy (32.40 ± 14.41 vs. 41.74 ± 45.61 h; P < .001) [7].…”
mentioning
confidence: 99%
“…Polymerase chain reaction (PCR) is well established for the diagnosis of "atypical" pathogens in severe community-acquired pneumonia [6] and for the study of ARDS with possible infectious etiology, namely for respiratory viruses (HSV and CMV), with virus load quantification, and also for Pneumocystis and Aspergillus [5]. In a retrospective case-control study in adult ICU patients with pneumonia and severe sepsis or septic shock, a strategy with bronchoalveolar lavage (BAL) cultures plus BAL M-PCR led to higher microbiological yield and less time to antibiotic therapy modification compared to a BAL culture strategy (32.40 ± 14.41 vs. 41.74 ± 45.61 h; P < .001) [7].…”
mentioning
confidence: 99%